Slanting EDGE method for modulation transfer function computation of X-Ray system - Saber Braim, Farhank (2013)
The edge method is commonly used to determine the modulation transfer function (MTF) of a straight edge image in radiography systems. Measurement of MTF by using slanting edge method is an important way to evaluate the quality of a slanted edge image, as it is difficult to acquire a straight image. Slanted edge image offers more data by reprojection of the data to the slanted line, and gives more points in the edge spread function (ESF). Straight and slanted edge images data were used to measure the ESF, the line spread function (LSF) and the presampled MTF using MATLAB R2011a program. Edge images were taken from a thick lead foil in a conventional radiographic screen-film system, and a , thick aluminium test objects with a thick lead in a Fuji computed radiography (FCR) system. Edge images of lead test devices provide higher MTFs than that of aluminiums. The MTF values of slanted edge images were compared to those obtained by straight edge images for spatial frequency range about . The MTF results of lead test devices for conventional and computed radiographic systems are similar, although the computed system has better MTF for spatial frequencies between and with a very low fluctuation due to the extremely small noise. However, for the conventional system has better and higher MTFs for both straight and slanted images. In the conventional radiographic system, the experimental MTF results are accepted by the method with the mean MTF difference of for the straight (0 degress) and the slanted with (2 degress) of edge images for spatial frequencies between and . On the other hand, the mean MTF difference for the straight (0 degress) and slanted (1 and 2 degress) resultant MTFs in the computed radiographic system are and respectively. The best MTF result was obtained from the slanted edge image (2 degress) in the FCR system.